(untitled) (Research, Society and Development, 2022)
The aim of the study is to evaluate the treatments for HIV/AIDS in different regions of Brazil in the year 2020. It is documentary research. Statistical data were used from the database of the Information Technology Department of the Unified Health System (DATASUS), from January to December of 2020, using filters for SUS hospital procedures, HIV/AIDS treatment and all regions do Brazil. The region with the highest number of treatments in 2020 was the Southeast region, corresponding to a total of 1551 treatments, accounting for 35.14% of the total. The region that presented the lowest number of treatments was the north region, showing a total of 160 of the total treatments in 2020. It is concluded that the treatment of HIV/AIDS in 2020, therefore, was more carried out in the Southeast region, which can be justified not only by the higher prevalence, but also by the greater distribution of health resources in this coverage area.